2002
DOI: 10.1121/1.1476685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and frequency disparity on gap discrimination

Abstract: Temporal discrimination was measured using a gap discrimination paradigm for three groups of listeners with normal hearing: (1) ages 18-30, (2) ages 40-52, and (3) ages 62-74 years. Normal hearing was defined as pure-tone thresholds < or = 25 dB HL from 250 to 6000 Hz and < or = 30 dB HL at 8000 Hz. Silent gaps were placed between 1/4-octave bands of noise centered at one of six frequencies. The noise band markers were paired so that the center frequency of the leading marker was fixed at 2000 Hz, and the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
91
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 42 publications
12
91
2
4
Order By: Relevance
“…Most interesting in light of the present results are the behavioral findings for older adults. This group often has poorer within-and across-channel gap detections than young adults; yet, age-group differences are much larger for acrosschannel than within-channel conditions (e.g., Lister & Roberts, 2005;Lister, et al, 2002).As within-and across-channel performance was not correlated in the present study (r = 0.22, p = 0.50) or others (Phillips & Smith, 2004), it is likely that different mechanisms are involved in the two tasks. The present study represents a first step in the investigation of the physiological underpinnings of across-channel gap detection.…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…Most interesting in light of the present results are the behavioral findings for older adults. This group often has poorer within-and across-channel gap detections than young adults; yet, age-group differences are much larger for acrosschannel than within-channel conditions (e.g., Lister & Roberts, 2005;Lister, et al, 2002).As within-and across-channel performance was not correlated in the present study (r = 0.22, p = 0.50) or others (Phillips & Smith, 2004), it is likely that different mechanisms are involved in the two tasks. The present study represents a first step in the investigation of the physiological underpinnings of across-channel gap detection.…”
contrasting
confidence: 52%
“…The shortest gap that a listener can detect (relative to the standard) is called a gap detection threshold (GDT). Psychophysical GDTs are influenced by a number of stimulus factors, including marker bandwidth (Eddins, Hall, & Grose, 1992;Snell, Ison, & Frisina, 1994), marker duration (He, Horwitz, Dubno, & Mills, 1999), monotic, diotic, or dichotic presentation modes (Gordon-Salant & Fitzgibbons, 1999;He, et al, 1999;Lister & Roberts, 2005), and the spectral similarity of the markers before and after the gap (Lister, Besing & Koehnke, 2002;Oxenham, 2000).…”
Section: Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the HI listeners in this study were on average older than the NH listeners in the study by Wojtczak et al (2012) used as a control group. A large number of studies have reported clear effects of age on gap detection and gap-duration discrimination for both within-channel and across-channel markers (Fitzgibbons and Gordon-Salant 1994;Schneider et al 1994;He et al 1999;Lister et al 2000Lister et al , 2002Lister and Roberts 2005). Since the NH and HI listeners compared in this study were not age-matched, some of the observed differences between their data may reflect poorer coding of temporal information or a reduced ability to integrate temporal information across frequency due to the age of the HI listeners.…”
Section: Age Versus Hearing Lossmentioning
confidence: 73%
“…However, deficits due to cochlear hearing loss have been shown in tasks involving comparisons of temporal information across frequency, although not consistently. Across-channel gap detection and gap-duration discrimination measured with frequency-disparate markers preceding and following silent gaps have been shown to be unaffected by hearing loss (Lister et al 2002;Lister and Roberts 2005). Similarly, the ability to detect a difference in temporal envelope patterns in the presence of an interfering modulation in the remote frequency region is comparable for the NH and HI listeners (Grose and Hall, 1996).…”
Section: Cochlear Hearing Loss and Processing Of Temporal Informationmentioning
confidence: 99%